An integrated 2H and 13C NMR study of gluconeogenesis and TCA cycle flux in humans - JONES, John G; SOLOMON, Michael A; COLE, Suzanne M; SHERRY, A. Dean; MALLOY, Craig R (American journal of physiology: endocrinology and metabolism, 2001)
Hepatic glucose synthesis from glycogen, glycerol, and the tricarboxylic acid (TCA) cycle was measured in five overnight-fasted subjects by (1)H, (2)H, and (13)C NMR analysis of blood glucose, urinary acetaminophen glucuronide, and urinary phenylacetylglutamine after administration of [1,6-(13)C2]glucose, (2)H2O, and [U-(13)C3]propionate.